Job satisfaction and organizational commitment among teachers: The moderating effect of demographic factors - Ng, Hooi Wen (2018)
The purpose of this study is to examine the relationship between job satisfaction and organizational commitment among public school teachers in Malaysia. Therefore this study could make important contribution to extant research in management and organizational behavior. Besides that, it increasing the understanding the importance’s role of teachers in the Malaysia education system. In the literature, it discussed about job satisfaction, organizational commitment and two of these variables’ relationship. This study generated 203 teachers become the respondents for this research. In this entire study, the data were gathered through questionnaires and was analyzed through statistical model such as reliability analysis, descriptive analysis, factor analysis, correlation analysis, simple regression analysis and hierarchy regression analysis. All these analysis are used to measure the purpose, research question, objective and hypothesis in this research study. As a conclusion, there is significant relationship between job satisfaction and organizational commitment.